Comércio e conflito: a privatização da segurança internacional e a regulação multinível do mercado de empresas militares privadas - Guedes, Henrique Lenon Farias (2016)
Hiring private armies or private security forces for a specific action, in favor of governments, corporations or civil society organizations – as opposed to the public formalities of war declaration between States with broad national goals –, generated one of the most relevant contemporary global markets. Yugoslavia, Colombia, Somalia, Nigeria, Ukraine, Iraq and the Levant: every insecure stage, after the end of the Cold War, counted on private military and security companies (PMSCs) for supporting roles or for staying at the backstage. Considering this innovative commercial aspect of today’s conflicts, this work counts on such non-State actors as protagonists, and its theme is the regulation of PMSCs. The problem that the dissertation examines is the insertion of the International Code of Conduct for Private Security Service Providers (ICoC) – launched in 2010, as part of the Swiss Initiative – in the multilevel governance of such a market, based especially on the works of Ernst-Ulrich Petersmann and Gunther Teubner on constitutionalism beyond the State. Through documental research and inductive methods, the text points out the main issues on the market for force and discusses the inapplicability or insufficiency of treaties that discipline trade, such as GATS, or conflict, such as the Geneva Conventions; besides, it sheds light on the current debate about a binding instrument at the United Nations and explains soft law initiatives, like the Montreux Document. Finally, it reads the ICoC and examines its advantages and limitations, with reference to reviewed literature. The research, therefore, aims at presenting the possibilities of regulating actors in need of hard law, based on theoretical contributions that reclaim the “constitutionalization of markets”. Keywords: Privatization of international security. Multilevel regulation.